Ewing’s sarcoma/primitive neuroectodermal tumour of the prostate a case report and literature review - Wu, Tao; Jin, Tao; Luo, Deyi; Chen, Lin; Li, Xiang (Canadian Urological Association Journal, 2013)
We present a case of Ewing’s sarcoma and primitive neuroectodermal tumour (PNET) of the prostate. A 29-year-old male presented with difficult defecation and anus distention; on magnetic resonance imaging scan of the pelvis, we found a prostate tumour. A transrectal ultrasound-guided needle biopsy confirmed the diagnosis. The patient underwent cystoprostatectomy and replacement ileocystoplasty and was followed by multi-agent chemotherapy. PNET/ Ewing’s sarcoma of the prostate is extremely rare. The prognosis is very poor, so we should pay enough attention to the differential diagnosis and treatment.